Image1_Submarine Landslide Susceptibility Mapping in Recently Deglaciated Terrain, Glacier Bay, Alaska.pdf - Nikita N. Avdievitch; Jeffrey A. Coe (2022)
Submarine mass wasting events have damaged underwater structures and propagated waves that have inundated towns and affected human populations in nearby coastal areas. Susceptibility to submarine landslides can be pronounced in degrading cryospheric environments, where existing glaciers can provide high volumes of sediment, while cycles of glaciation and ice-loss can damage and destabilize slopes. Despite their contribution to potential tsunami hazard, submarine landslides can be difficult to study because of limited access and data collection in underwater environments. Here we present a method to quantify and map the submarine landslide susceptibility of sediment-covered slopes in Glacier Bay, Glacier Bay National Park and Preserve, Alaska, using multibeam-sonar bathymetric digital elevation models (DEMs) and historical maps of glacial extents over the last ∼250 years. After mapping an inventory of >7,000 landslide scarps in submarine sediments, we filtered the inventory by size to account for limitations in DEM resolution and spatial scales relevant to tsunami hazards. We then assessed landslide concentration, accounting for the age of the initial exposure of submarine slopes by deglaciation. We found a positive correlation between landslide concentration and deglaciation age, which we interpreted as a mean landslide accumulation rate over the period of record. Local deviations from this rate indicated differences in susceptibility. Additionally, we accounted for some of the effect of material and morphometric properties by estimating the submarine bedrock-sediment distribution using a morphometric model and assessing the relationship between slope angle and landslide incidence. Finally, we supplemented our susceptibility assessment with a geomorphic component based on the propensity of active submarine fans and deltas to produce landslides. Thus, our map of submarine landslide susceptibility incorporates three components: age-adjusted landslide concentration, slope angle, and geomorphology. We find that ...